Management of sustainability transitions through planning in shrinking resource city contexts: an evaluation of Yubari City, Japan. Issue 4 (4th July 2018) - Mabon, Leslie; Shih, Wan-Yu
ABSTRACT: This paper evaluates the planning competences required to enact a managed transition to sustainability at the municipal level for cities facing population, economic and employment decline. Drawing on the 'shrinking cities' literature, we argue consolidation of the built environment can become a focal point for sustaining citizen welfare when transitioning cities that are facing decline, especially those previously reliant on resource industries. We evaluate the former coal mining city of Yubari, Japan, which is developing a consolidated urban form with the aim of creating a 'sustainable' future city. Findings from interviews and content analysis of Yubari's planning policy indicate, however, that to translate 'shrinking' a city into a managed transition, spatial planning must be accompanied by a wider range of social policy measures and strong cross-sectoral engagement. We also caution that the unique geographical and political context of Yubari mean its model may not be directly replicable in other contexts.